VARIASI KEASAMAN DAN KAPASITAS PENYANGGA KAYU TAMPUI BERAS ( Baccaurea macrocarpa (Miq.) Muell.Arg.) dan MANGGIS HUTAN ( Garcinia cornea Miq.) - Krisdianto (BRIN Publishing, 2013)
Wood acidity signifies an important factor that inflicts impact on metal corrosion and gives effect on adhesive bonding quality. Wood acidity varies not only between species, but also at different parts in the same tree. This paper studies the wood pH and buffering capacity at various positions in the same tree of two potential species from Rian. Those wood species are locally known as tampui beras (Baccaurea macrocarpa (Miq.) Muell. Arg.) and manggis butan (Garcinia cornca Miq.). The pH was determined using pH meter on the liquid of bot-water-extracted sawdust of the corresponding wood, while buffering capacity was measured by acid and base titration. The result shows that in average, acidity of tampui beras wood (5.2) is stronger than that of manggis hutan (6.3). Both wood species are classified as acid wood with pH less than 7. With respect to the tree height, sample taken from bottom part has the lowest pH value, while based on lateral position at the stem, progressing from the bark in depth to the pith the sapwood is higher in pH value than the beartwood and transition area. In every wood sample tested, acid buffer capacity is higher than base capacity.